Method for producing scratch-resistant bio-additive for use in plastics, and scratch-resistant bio-additive for use in plastics produced by the method

JP2025505659AActive Publication Date: 2025-02-28LIGNUM INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024547003
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-24
Filing Date
2023-02-22
Publication Date
2025-02-28
Estimated Expiration
2043-02-22

AI Technical Summary

Benefits of technology

【0026】 本発明に係るプラスチック添加用耐スクラッチ性バイオ添加剤の製造方法は、安価な非食用リグノセルロース系バイオマスを特定の条件による化学的処理工程によって、非食用リグノセルロース系バイオマスから高い生産費用なしに工程が簡単でありながらも耐スクラッチ性が発現できるようにリグノセルロースが機能化され、親油化及び疎水性に優れるため、プラスチック製造時に分散特性が改善された、プラスチック添加用耐スクラッチ性バイオ添加剤を高収率で製造することができるという利点を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505659000001_ABST
    Figure 2025505659000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a scratch-resistant bio-additive for plastics, and a scratch-resistant additive for plastics produced thereby, and more particularly to a method for producing an oleophilic scratch-resistant bio-additive for plastics from a hydrophilic lignocellulosic biomass, and a scratch-resistant bio-additive for plastics produced thereby.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a scratch-resistant bio-additive for use in plastics, and a scratch-resistant bio-additive for use in plastics produced thereby. More particularly, the present invention relates to a method for producing a scratch-resistant bio-additive for use in plastics that replaces conventional high-density inorganic fillers and has improved scratch resistance, and a scratch-resistant bio-additive for use in plastics produced thereby. [Background technology]

[0002] In recent years, with the advent of new fuel efficiency and exhaust gas regulations, there has been an increased demand for lighter vehicles. To address this demand, many vehicle parts are now made of plastic.

[0003] For example, a plastic automobile door module is composed of outer and inner panels, door trim, etc., which are frequently used by passengers, and therefore not only mechanical performance but also aesthetic and emotional aspects of the plastic surface design are important.

[0004] In particular, as vehicles have become more luxurious in recent years, the beauty of the vehicle surface may become an important factor for consumers when purchasing a vehicle. In this case, an important factor determining the beauty of the vehicle surface is the absence of discoloration of the surface due to scratches.

[0005] Polypropylene (PP) is a typical plastic material used for general vehicle interior materials. It has the advantages of low specific gravity (about 0.9), chemical resistance, and excellent moldability. Recently, products that have improved stiffness and scratch hardness by adding inorganic fillers such as talc to polypropylene have been commercially available.

[0006] However, talc has low bonding strength with the polymer matrix in plastics, so it can easily separate due to surface deformation and damage, and the exposed white talc particles have the problem of increasing scratch visibility due to light reflection.To solve this problem, technologies to improve scratch resistance using rubber, silicon compounds, fluororesins, amide-based additives, etc. have been developed.

[0007] However, rubber, which is used to improve scratch resistance, has a limitation of deteriorating the texture of the surface, and silicon compounds have a limitation of not only dispersibility problems during compounding due to reduced process convenience and reduced compatibility with polypropylene, but also degradation of surface properties such as formation of a viscous oil film on the plastic surface due to migration of additives during long-term use. In addition, most of the additives are petroleum-based materials. Therefore, due to various environmental problems caused by global warming, it is urgent to replace plastics with environmentally friendly bio-based materials to achieve carbon neutrality and solve the environmental pollution problem caused by the excessive use of plastic products.

[0008] Related to this, Korean Patent Publication No. 10-1889744, which is a related art for plastic additives, describes a technology in which lignin extract from the pulp process and pulp are mechanically pulverized to produce nanocellulose modified with a silane compound, and then these are mixed to produce a modified lignin-nanocellulose composite, which is then mixed with a maleic anhydride-grafted polypropylene material to produce a lignin composite for plastic production. However, this technology also contains expensive nanocellulose and the process is very complicated, so it has limitations in its application to materials for general-purpose plastic production.

[0009] Therefore, there is an even greater need to develop scratch-resistant bio-additives for use in plastics that have scratch resistance and excellent lipophilicity and hydrophobicity, thereby improving the dispersion characteristics when used as a plastic additive, as an environmentally friendly bio-material that is a departure from the petroleum-based materials used in plastic manufacturing. Summary of the Invention [Problem to be solved by the invention]

[0010] The technical problem to be solved by the present invention is to provide a novel method for producing a scratch-resistant bioadditive for use in plastics, which can solve the above problems and has high binding strength with a polymer matrix by using non-edible lignocellulosic biomass as a raw material and has improved scratch resistance when added to plastics, and has excellent lipophilicity and hydrophobicity, which improves dispersion characteristics and compatibility during plastic production.

[0011] Another technical objective of the present invention is to provide a scratch-resistant bio-additive for plastics having improved scratch resistance, which is produced by the above-mentioned production method, a plastic composition containing the same, and a scratch-resistant plastic product containing the plastic composition. [Means for solving the problem]

[0012] In order to achieve the above object, the present invention provides a method for producing a lignin-cellulose microfibril (MFC) composite by adding an acid to a lignocellulosic biomass to hydrolyze at least a part of the hemicellulose in the lignocellulosic biomass and convert at least a part of the cellulose into microfibrillated cellulose (MFC), and (b) separating the cellulose microfibril (MFC) in the lignin-cellulose microfibril (MFC) composite obtained from the above step (a). The present invention provides a method for producing a scratch-resistant bio-additive for use in plastics, the method comprising the steps of: (a) selectively hydrolyzing at least a portion of the amorphous domains of cellulose to obtain a lignin-cellulose microfibril (MFC) composite having improved crystallinity of the cellulose microfibril (MFC); (b) adding a base to the lignin-cellulose microfibril (MFC) composite having improved crystallinity of the cellulose microfibril (MFC) obtained in step (b) to neutralize residual acidic components, and then removing water-soluble substances to obtain solid particles; and (c) pulverizing the solid particles obtained in step (c).

[0013] The present invention also provides a method for producing a scratch-resistant bio-additive for use in plastics, the method comprising the steps of: (a) adding an acid to lignocellulosic biomass to hydrolyze at least a portion of the hemicellulose in the lignocellulosic biomass and convert at least a portion of the cellulose into microfibrillated cellulose (MFC), and selectively hydrolyzing at least a portion of the amorphous domains of the microfibrillated cellulose (MFC) to produce a lignin-cellulose microfibril (MFC) composite having increased crystallinity; (b) adding a base to the lignin-cellulose microfibril (MFC) composite obtained from step (a) to neutralize residual acidic components, and then removing water-soluble substances to obtain solid particles; and (c) pulverizing the solid particles obtained from step (b).

[0014] As one example, in the step (a), the acid may be selected from an organic acid having 1 to 20 carbon atoms; or an inorganic acid selected from sulfuric acid, hydrochloric acid, phosphoric acid, and nitric acid, or a mixture thereof; or a mixture of the organic acid and an inorganic acid; or a mixture of a mixture of the organic acid and an inorganic acid.

[0015] As one embodiment, the step (a) may be carried out by: i) adding an aqueous acid solution and subjecting the lignocellulosic biomass to a heating and / or pressure treatment; ii) adding an aqueous acid solution and subjecting the lignocellulosic biomass to a steam explosion; or iii) combining the heating and pressure treatment with the steam explosion.

[0016] As one example, the step of selectively hydrolyzing at least a portion of the amorphous domains of the cellulose microfibril (MFC, microfibrillated cellulose) in the lignin-cellulose microfibril (MFC) complex to increase the crystallinity of the cellulose microfibril (MFC) to obtain a lignin-cellulose microfibril (MFC) complex may be performed under higher temperature and / or pressure conditions than the previous step of adding an acid to a lignocellulosic biomass to hydrolyze at least a portion of the hemicellulose in the lignocellulosic biomass and convert at least a portion of the cellulose into cellulose microfibril (MFC, microfibrillated cellulose) to obtain a lignin-cellulose microfibril (MFC) complex.

[0017] As an example, the acid in step (a) may be any one selected from hydrochloric acid, sulfuric acid, and nitric acid, or a mixture thereof, and the concentration of the acid may be in the range of 0.5 to 70 wt %.

[0018] As an example, the base used in the step of neutralizing the residual acidic components may be at least one selected from sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), lithium hydroxide (LiOH), calcium carbonate (CaCO3), potassium carbonate (K2CO3), sodium carbonate (Na2CO3), potassium bicarbonate (KHCO3), magnesium hydroxide (Mg(OH)2), calcium oxide (CaO), magnesium oxide (MgO), and sodium bicarbonate (NaHCO3), or a mixture thereof.

[0019] As one example, the solid particles obtained by the step of obtaining the solid particles may have a hemicellulose content of 5 weight (wt%) or less, preferably 3 weight (wt%) or less, and more preferably 2 weight (wt%) or less, based on the total of lignin, cellulose, and hemicellulose-derived components.

[0020] As one embodiment, the solid particles obtained by the step of obtaining the solid particles may contain 1 wt% to 99 wt% of lignin-derived components and 1 wt% to 99 wt% of cellulose-derived components, based on the total amount of lignin, cellulose, and hemicellulose-derived components.

[0021] As an example, the length of the cellulose microfibrils (MFC) in the pulverized solid particles from the step of pulverizing the solid particles may be in the range of 50 nm to 100 μm, preferably 100 nm to 50 μm, and more preferably 300 nm to 20 μm.

[0022] The present invention also provides a scratch-resistant bio-additive for use in plastics, which is produced by the method for producing the scratch-resistant bio-additive for use in plastics according to the present invention.

[0023] The present invention also provides a scratch-resistant bio-additive for plastics, comprising a lignin-cellulose microfibril (MFC) composite in which at least a portion of cellulose is converted into cellulose microfibrillated cellulose (MFC) by acid treatment and neutralization of lignocellulosic biomass, the MFC composite containing 1 wt% to 99 wt% of lignin-derived components and 1 wt% to 99 wt% of cellulose-derived components based on the total sum of lignin, cellulose and hemicellulose-derived components, a hemicellulose content of 5 wt% or less based on the total sum of lignin, cellulose and hemicellulose-derived components, and a length of the cellulose microfibril (MFC) in the lignin-cellulose microfibril (MFC) composite in the range of 50 nm to 100 μm.

[0024] The present invention also provides a plastic composition including the scratch-resistant bio-additive for use in plastics, and preferably provides a scratch-resistant plastic composition, characterized in that the plastic composition includes the scratch-resistant bio-additive for use in plastics in an amount of 0.1 to 60 wt % based on the total weight of the plastic composition.

[0025] The present invention also provides a scratch-resistant product comprising the plastic composition. Effect of the Invention

[0026] The method for producing a scratch-resistant bio-additive for use in plastics according to the present invention has the advantage that a scratch-resistant bio-additive for use in plastics can be produced in high yield from inexpensive non-edible lignocellulosic biomass through a chemical treatment process under specific conditions, in which lignocellulose is functionalized so that scratch resistance can be expressed from the non-edible lignocellulosic biomass without high production costs, the process is simple, and the scratch-resistant bio-additive has excellent lipophilicity and hydrophobicity properties, thereby improving dispersion properties during plastic production.

[0027] In addition, the scratch-resistant bio-additive for plastics according to the present invention has an effect of improving scratch resistance when added to plastics, and can therefore be applied to products that require scratch resistance, such as materials for vehicles, buildings, and packaging. In addition to its scratch-resistant effect, the bio-additive has a filler function that can replace talc, and when replacing talc with a high specific gravity, it has the advantage of making plastics lighter.

[0028] Furthermore, the scratch-resistant bio-additive for adding to plastics obtained from lignocellulosic biomass according to the present invention has the advantage of being very environmentally friendly compared to petroleum-derived materials, since it is a plant-derived material. [Brief description of the drawings]

[0029] [Figure 1]FIG. 1 shows (a) the hierarchical structure of biomass-derived cellulose and (b) the structure of cellulose microfibrils containing crystalline and amorphous domains. [Diagram 2] 1 is an electron microscope photograph of the scratch resistance additive of Production Example 1 before pulverization. [Diagram 3] 1 is an electron microscope photograph of the scratch resistance additive of Production Example 1 after pulverization. [Figure 4] 1 shows the results of evaluation of scratch resistance of test pieces according to Comparative Examples 1 and 2 and Example 1 of the present invention. [Diagram 5] 1 is a photograph showing the particle size distribution of the scratch resistance additive according to Production Example 1 after pulverization. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Throughout the specification of this application, when a part "comprises" a certain element, this does not mean to exclude other elements, but means that it may further include other elements, unless specifically stated to the contrary.

[0031] The production method according to the present invention will now be described in more detail.

[0032] The method for producing the scratch-resistant bio-additive for plastics according to the present invention includes the steps of: (a) adding an acid to lignocellulosic biomass to hydrolyze at least a part of the hemicellulose in the lignocellulosic biomass and converting at least a part of the cellulose into microfibrillated cellulose (MFC) to obtain a lignin-cellulose microfibrillated (MFC) composite; and (b) isolating the cellulose microfibrillated (MFC) in the lignin-cellulose microfibrillated (MFC) composite obtained from the step (a). (c) adding a base to the lignin-cellulose microfibril (MFC) composite having improved crystallinity of cellulose microfibril (MFC) obtained in step (b) to neutralize residual acidic components, and then removing water-soluble substances to obtain solid particles; and (d) grinding the solid particles obtained in step (c).

[0033] As a first step, the step (a) is a step of adding an acid to the raw material lignocellulosic biomass to hydrolyze at least a portion of the hemicellulose in the lignocellulosic biomass and convert at least a portion of the cellulose into microfibrillated cellulose (MFC), thereby obtaining a lignin-cellulose microfibrillated (MFC) composite.

[0034] The lignocellulosic biomass in step (a) according to the present invention is a material containing lignin and at least one of cellulose and hemicellulose, and preferably contains all of lignin, cellulose, and hemicellulose. Such lignocellulosic biomass may be a variety of biomass, such as herbaceous biomass, woody biomass (conventional wood) such as coniferous or broad-leaved trees, or rice straw, corn cobs, coconut shells, and sugar cane.

[0035] Here, the addition of acid in step (a) of the present invention destroys the strong crystallization structure between lignin and cellulose in the biomass, hydrolyzes at least a portion of the hemicellulose, and converts at least a portion of the cellulose fibers, preferably 10% or more of the cellulose components contained in the biomass, more preferably 20% or more, more preferably 30% or more, more preferably 40% or more, more preferably 50% or more, more preferably 60% or more, more preferably 70% or more, more preferably 80% or more, more preferably 90% or more, and more preferably 95% or more, into a cellulose microfibrillated cellulose (MFC) form, and the acid treatment chemically bonds lignin to at least a portion of the cellulose microfibril (MFC) to form a polymeric lignin-cellulose microfibril (MFC) complex.

[0036] In other words, the present invention provides a scratch-resistant bio-additive in which the cellulose microfibrillated cellulose (MFC) in the lignin-cellulose microfibrillated MFC complex obtained by acid treatment, which is the main component of the scratch-resistant bio-additive, exerts a scratch-resistant effect, and in this case, the lignin that has been hydrophobized by modification through acid treatment can uniformly disperse the cellulose microfibrillated cellulose (MFC) in plastic, making it more capable of functioning as a scratch-resistant plastic additive. This has the advantage of being able to provide a more environmentally friendly and economical plastic additive through a component derived from lignocellulose-based biomass, which is a low-cost bio-raw material.

[0037] Here, the cellulose contained in the lignocellulosic biomass is a fibrous material in which linear chains linked by β-glycosidic bonds of the unit D-glucose (Dκ-glucose) are stacked. Referring to FIG. 1(a) showing the hierarchical structure of biomass-derived cellulose, the cellulose fiber includes microfibril bundles composed of microfibrils, and the microfibril includes elementary fibrils, which are the lowest level structure.

[0038] Hereinafter, in the present invention, microfibrillated cellulose (MFC) refers to microfibrillated cellulose fibers having a fiber width (thickness) of 1 μm or less, preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less, which are obtained when cellulose fibers contained in lignocellulosic biomass such as wood (wood bulk) are defibrated. As shown in FIG. 1(a), The term "fibrous bundle" should be understood as including microfibril.

[0039] At this time, the cellulose microfibrillated (MFC) has a structure including a crystalline domain and an amorphous domain, as shown in FIG. 1(b).

[0040] Meanwhile, the lignocellulosic biomass used as a raw material in step (a) may be pulverized after a drying process. In this case, in order to ensure uniformity in the subsequent processes, the pulverized size is preferably 20 mm or less, more preferably in the range of 10 to 0.001 mm.

[0041] Here, in the step (a), an acid serving as a catalyst hydrolyzes at least a portion of the hemicellulose in the lignocellulosic biomass, and converts at least a portion of the cellulose into microfibrillated cellulose (MFC).

[0042] In this case, the acid used in step (a) can be selected from an organic acid having 1 to 20 carbon atoms; an inorganic acid selected from sulfuric acid, hydrochloric acid, phosphoric acid, and nitric acid, or a mixture thereof; a mixture of the organic acid and an inorganic acid; or a mixture of a mixture of the organic acid and an inorganic acid.

[0043] In this case, in the case of the organic acid, a monocarboxylic acid, a biscarboxylic acid, a triscarboxylic acid, a tetracarboxylic acid, or the like can be used as a carbon compound containing a carboxylic acid, depending on the number of the carboxylic acid, and an organic acid having 1 to 20 carbon atoms, preferably an organic acid having 1 to 15 carbon atoms, depending on the number of carbon atoms, can be used, and more preferably, acetic acid, formic acid, propionic acid, or the like can be used.

[0044] As a preferred example of the acid component used as the inorganic acid, any one selected from hydrochloric acid, sulfuric acid, and nitric acid, or a mixture thereof, can be used. The preferred acid concentration is in the range of 0.5 to 70 wt%, more preferably 0.6 to 65 wt%, and even more preferably 0.7 to 60 wt%, based on the total content of the aqueous solution containing the pulverized biomass and the acid. As an even more preferred example, sulfuric acid in the range of 0.5 to 70 wt%, more preferably 0.6 to 65 wt%, and even more preferably 0.7 to 60 wt%, based on the total content of the aqueous solution containing the pulverized biomass and the acid, can be used.

[0045] Here, the content of the strong acid is, for example, when 75% (v / v) sulfuric acid is added, the sulfuric acid concentration can be in the range of 0.5wt% to 70wt%, preferably 0.6wt% to 65wt%, based on the final concentration (based on the total content of the pulverized biomass and the aqueous solution). The above ratio can be used by changing the optimum conditions in various ways depending on the type of biomass, and if hydrochloric acid is used, a similar range of moles can be calculated and used, and even if a mixture of sulfuric acid and hydrochloric acid is used, the amount of strong acid added can be appropriately determined based on the above range.

[0046] In addition, the step (a) of the present invention can be carried out by: i) adding an acid aqueous solution and subjecting the lignocellulosic biomass to a heating and / or pressure treatment, or ii) adding an acid aqueous solution and subjecting the lignocellulosic biomass to a steam explosion, or iii) combining the heating and pressure treatment and the steam explosion.

[0047] Here, in the hydrolysis process of step (a), i) the heating and / or pressurizing process may include a process of reacting a mixture containing lignocellulosic biomass and an aqueous acid solution at 80 to 250°C, preferably 90 to 150°C, for 2 minutes to 2 days, preferably 5 minutes to 5 hours, at normal pressure or 10 atmospheres or less, followed by reducing the pressure and filtering the solid matter, and ii) the steam explosion process may include a process of reacting a mixture containing lignocellulosic biomass and an aqueous acid solution using steam at 100 to 250°C, preferably 120 to 190°C, for 5 minutes to 5 hours, preferably 10 minutes to 1 hour, followed by instantaneous reduction in pressure.

[0048] At this time, the concentration of the acid to be added may be in various ranges depending on the type of acid and conditions such as reaction temperature and pressure.

[0049] Meanwhile, the step (b) is a step of selectively hydrolyzing at least a portion of the amorphous domain of the cellulose microfibril (MFC) in the lignin-cellulose microfibril (MFC) composite obtained in the step (a) to obtain a lignin-cellulose microfibril (MFC) composite having increased crystallinity of the cellulose microfibril (MFC). Referring to FIG. 1(b), the cellulose microfibril (MFC) includes a crystalline domain and an amorphous domain. At this time, by hydrolyzing at least a portion of the amorphous domain in the cellulose microfibril (MFC), the fibrous structure of the cellulose microfibril (MFC) is destroyed and the crystallinity of the cellulose microfibril (MFC) is improved, thereby improving the scratch resistance when used as a bioadditive for plastics, and improving the rigidity and strength of the polymer.

[0050] The partial hydrolysis reaction of the amorphous domain of the cellulose microfibril (MFC) in the step (b) can be carried out, for example, by subjecting the reactant obtained in the step (a) to a high temperature and high pressure reaction. In this case, more preferably, the step (b) can be carried out under higher temperature and / or higher pressure conditions than the step (a).

[0051] Through steps (a) and (b) of the present invention, the molecular structure of the lignin-cellulose microfiber (MFC) complex in the biomass is changed, and many of the hydroxyl groups (-OH) and carboxyl groups (-COOH) present therein can be removed and hydrophobized through dehydration and decarboxylation, respectively. Hydrophobic solid particles having various structures and physical properties can be produced by changing the weight ratio between the lignin and cellulose microfiber (MFC) in the complex and by condensation / polymerization reactions between functional groups.

[0052] To explain this in more detail, by adding an acid component such as hydrochloric acid or sulfuric acid to the lignocellulosic biomass and reacting it through stirring, the hydrophilic cellulose, one of the substances that make up the lignocellulosic biomass, is converted into cellulose microfibers (MFC), the amorphous domains of the cellulose microfibers (MFC) are selectively hydrolyzed to improve crystallinity, and the complex is hydrophobized by dehydration of the hydroxyl groups (R-OH groups) of the lignin / cellulose microfiber (MFC) molecules and decarboxylation of the carboxyl groups (R-COOH). In addition, condensation / polymerization reactions take place between various functional groups present in the lignin and cellulose microfiber (MFC) molecules, forming hydrophobic solid particles of polymers with very complex structures.

[0053] In this regard, in the present invention, by controlling the chemical reaction conditions (reaction time, reaction temperature, acid concentration, reaction pressure, etc.) by the acid component, the reaction conditions for producing cellulose microfibers (MFC) and the reaction conditions for partial hydrolysis of the amorphous domains of cellulose microfibers (MFC) are appropriately adjusted, so that the ratio of lignin-cellulose microfibers (MFC) in solid particles including the lignin-cellulose microfiber (MFC) complex obtained subsequently can be variously adjusted, thereby producing bio-based scratch-resistant additives for plastics with various physical properties.

[0054] Meanwhile, the steps (a) and (b) can be carried out sequentially in the same reactor depending on time, or can be carried out in separate reactors, and the reaction product obtained after carrying out the step (a) can be introduced into a separate reactor to carry out the step (b). This can be determined comprehensively in consideration of the reaction conditions, the size of the reactants, economic efficiency, etc.

[0055] In the present invention, the steps (a) and (b) may be performed with a time lag, that is, the step (a) may be performed first and then the step (b). Alternatively, the steps (a) and (b) may be performed simultaneously.

[0056] Here, when steps (a) and (b) are performed simultaneously, this corresponds to the case where the reaction conditions for steps (a) and (b) are the same, and thus steps (a) and (b) correspond to the steps of: adding an acid to lignocellulosic biomass to hydrolyze at least a portion of the hemicellulose in the lignocellulosic biomass and converting at least a portion of the cellulose into cellulose microfibril (MFC, microfibrillated cellulose), and selectively hydrolyzing at least a portion of the amorphous domains of the cellulose microfibril (MFC, microfibrillated cellulose) to produce a lignin-cellulose microfibril (MFC) composite with enhanced crystallinity of the cellulose microfibril (MFC).

[0057] Meanwhile, the step (c) in the present invention is a step of adding a base to the lignin-cellulose microfiber (MFC) composite obtained in the step (b) to neutralize the residual acidic components, and then removing the water-soluble substances to obtain solid particles; if the residual acidic components remain in the subsequent process, they may adversely affect the production and physical properties of plastics, so they are removed by neutralization using a base.

[0058] In this case, the base used may be at least one selected from sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia (NH3), lithium hydroxide (LiOH), calcium carbonate (CaCO3), potassium carbonate (K2CO3), sodium carbonate (Na2CO3), potassium bicarbonate (KHCO3), magnesium hydroxide (Mg(OH)2), calcium oxide (CaO), magnesium oxide (MgO), and sodium bicarbonate (NaHCO3), or a mixture thereof, but any type of base may be used as long as it can neutralize the acid component.

[0059] In this case, in the present invention, before neutralizing the residual acidic components between steps (b) and (c), a step of washing the acidic components remaining in the modified lignin-cellulose microfiber (MFC) composite obtained through step (b) with water may be further included, and the acid contained in the aqueous solution obtained after washing may be recovered and reused.

[0060] In addition, in the present invention, the step of removing water-soluble substances from the neutralized reactant in step (c) is a step of removing the water-soluble substances contained in the reactant by dehydrating and washing the neutralized reactant with water to obtain solid particles, where the water-soluble substances are any one or a mixture of water-soluble substances containing residual sugar components derived from biomass, substances derived from the acid addition process, and substances derived from the base addition process, and refer to components that can be dissolved in an aqueous solution.

[0061] The removal of the water-soluble substances can be carried out, for example, by a washing process using an aqueous solution. More specifically, the product obtained by the neutralization step in step (c) can be washed with an aqueous solution and then inputted into an acidic component and a basic component to remove water-soluble salts obtained by the washing process, and some of the saccharides hydrolyzed among the components in the lignocellulosic biomass. As a result, by removing a certain amount of polysaccharides hydrolyzed by the acid component, it is possible to obtain solid particles in which at least 30% by weight, preferably 40% by weight, more preferably 50% by weight, even more preferably 60% by weight, and even more preferably 70% by weight of the lignocellulosic biomass is converted based on the dry weight of the input biomass, based on the total weight of the solid particles obtained.

[0062] In this case, the solid particles obtained through step (c) may have a hemicellulose content of 5 weight (wt%) or less, preferably 3 weight (wt%) or less, and more preferably 2 weight (wt%) or less, based on the total of lignin, cellulose, and hemicellulose-derived components.

[0063] In other words, through steps (a) and (b), most of the hemicellulose contained in the biomass is removed, and the resulting solid particles contain lignin and cellulose microfibril (MFC) as their main components, which form a lignin-cellulose microfibril (MFC) complex and serve as a bio-additive for use in plastics.

[0064] On the other hand, the solid particles obtained through step (c) may contain 1 wt% to 99 wt% of lignin-derived components, based on the total amount of lignin and cellulose- and hemicellulose-derived components, preferably 20 wt% to 80 wt%, more preferably 30 wt% to 70 wt%, and even more preferably 40 wt% to 60 wt%.

[0065] Furthermore, the solid particles obtained through step (c) may contain cellulose-derived components in an amount of 1 wt% to 99 wt%, preferably 20 wt% to 80 wt%, more preferably 25 wt% to 75 wt%, and even more preferably 30 wt% to 70 wt%, based on the total amount of lignin and cellulose and hemicellulose-derived components.

[0066] Furthermore, the solid particles obtained through step (c) preferably contain 1 wt% to 99 wt%, preferably 20 wt% to 80 wt%, of lignin-derived components, and 1 wt% to 99 wt%, preferably 20 wt% to 80 wt%, of cellulose-derived components, based on the total amount of lignin and cellulose- and hemicellulose-derived components.

[0067] Meanwhile, the step (d) in the present invention is a step of pulverizing the solid particles obtained in the step (c), which is performed in order to prepare a powder form that is more dispersible and has improved compatibility with other additives and is easy to handle when used as a scratch-resistant additive for plastics. The pulverization method can be any known pulverization method including a ball mill, a SPEX mill, and a nano mill, without any restrictions, and the particle size obtained after pulverization can be in the range of 0.05 to 200 μm.

[0068] Here, a step of drying the moisture in the solid particles may be carried out before the pulverization in step (d), and the moisture content in the solid particles can be reduced to less than 5% by weight through the drying step.

[0069] In the present invention, the length of the cellulose microfibrils (MFC) in the solid particles pulverized in the step (d) may be in the range of 50 nm to 100 μm, preferably 100 nm to 50 μm, and more preferably 300 nm to 20 μm.

[0070] Meanwhile, the present invention can provide a scratch-resistant bio-additive for plastics, which is prepared by the method described above.

[0071] More specifically, the present invention can provide a scratch-resistant bio-additive for plastics, comprising the lignin-cellulose microfibril (MFC) composite described above.

[0072] More specifically, the present invention provides a scratch-resistant bio-additive for plastics, which comprises a lignin-cellulose microfibril (MFC) composite in which at least a portion of cellulose is converted into cellulose microfibrillated cellulose (MFC) through an acid treatment and neutralization process of lignocellulosic biomass, the MFC composite containing 1 wt% to 99 wt% of lignin-derived components and 1 wt% to 99 wt% of cellulose-derived components based on the total sum of lignin, cellulose, and hemicellulose-derived components, the hemicellulose content is 5 wt% or less based on the total sum of lignin, cellulose, and hemicellulose-derived components, and the length of the cellulose microfibril (MFC) in the lignin-cellulose microfibril (MFC) composite is in the range of 50 nm to 100 μm.

[0073] The composition of the scratch-resistant bio-additive for plastics according to the present invention is the same as that described in detail in the method for manufacturing the scratch-resistant bio-additive according to the present invention, and the description thereof is referred to above.

[0074] The present invention also provides a plastic composition including the scratch-resistant bio-additive for plastics, and preferably, the plastic composition may include the plastic composition in an amount of 0.1 to 60 wt % based on the total weight.

[0075] In other words, when manufacturing a plastic composite material containing the scratch-resistant bio additive according to the present invention, it is possible to provide improved scratch resistance while maintaining the physical properties of existing petroleum-based plastics, which has the advantage of greatly increasing its commercial applicability.

[0076] Typically, cellulose and lignin components separated from lignocellulosic biomass can cause various problems during plastic production due to their hydrophilicity or fibrous structure, making them less versatile. However, the scratch-resistant bioadditive for plastics obtained by the present invention has the advantages of improving the crystallinity of the cellulose microfibers (MFC) by treating the lignocellulosic biomass with an acid to convert the cellulose into cellulose microfibers (MFC) and removing hemicellulose, and hydrolyzing the amorphous domains of the cellulose microfibers (MFC), making the additive more hydrophobic, and facilitating compatibility with general-purpose plastics by minimizing the fibrous structure, ultimately improving the scratch-resistant surface properties of plastic materials.

[0077] In addition, the specific process for each step used in the present invention does not require separate purification of cellulose and lignin, and can directly use lignocellulosic biomass as a raw material, and the processes of removing hemicellulose and partially hydrolyzing the amorphous domains of cellulose microfibers (MFC) can be carried out sequentially or simultaneously in one reactor, thereby providing the advantage of being able to produce scratch-resistant bioadditives in a simpler and more economical manner than conventional techniques with a high yield.

[0078] Meanwhile, the scratch-resistant bio-additive for plastics according to the present invention may be contained in an amount of 0.1 to 60% by weight, preferably 0.5 to 30% by weight, more preferably 0.8 to 20% by weight, and most preferably 2 to 15% by weight, based on the total weight of the plastic material.

[0079] The scratch-resistant bio-additive according to the present invention can be added to any plastic that requires scratch resistance and can be mixed and used. Preferably, one or more plastic components selected from the group consisting of polypropylene (PP), polyethylene (PE), polyvinyl chloride (PVC), polystyrene (PS), polyurethane, polycarbonate, polyurea, polyimide, polyamide, polyacetal, polyester, nylon, epoxy resin, acrylic resin, acrylonitrile-butadiene-styrene (ABS), polylactic acid, polybutylene adipate terephthalate, and polybutylene succinate can be used.

[0080] For example, 0.1 to 30% by weight of the bioadditive obtained by the present invention and other additives are mixed with polypropylene (PP) to prepare a scratch-resistant plastic composite resin composition, which can be used for injection / extrusion to produce scratch-resistant plastic products.

[0081] In addition, the plastic composite resin composition may further contain various additives such as antioxidants, colorants, release agents, lubricants, and rubbers, and the amounts of these additives used may be appropriately adjusted depending on various factors including the desired end use and properties.

[0082] In conclusion, the bioadditive produced by the production method according to the present invention is a material obtained by removing most of the hemicellulose component, which has poor thermal decomposition properties, and subjecting the lignin component and the cellulose microfiber (MFC) component to various reaction conditions such as reaction time, temperature and pressure under acid catalyst conditions, for example, dehydration reaction / decarboxylation reaction / condensation reaction / polymerization reaction. Structurally, it is not a single compound but a complex mixture of various polymer components. The binding strength between the modified lignin and the cellulose microfiber (MFC) is strengthened, and the lignin component is further hydrophobicized. Therefore, when used as a plastic additive material, the crystallinity, dispersibility and compatibility with matrix polymers of the material are improved, and scratch resistance is exhibited over the entire plastic surface.

[0083] The present invention also provides a scratch-resistant plastic product comprising the plastic composition.

[0084] Hereinafter, the present invention will be described in more detail through examples to help the understanding of the present invention. However, the examples described in the present invention may be modified in various conditions. Therefore, the scope of the present invention is not limited to the following examples. The following examples of the present invention are merely intended to provide a more detailed explanation to those skilled in the art.

[0085] <Production of lignin-cellulose microfibril (MFC) composites by acid treatment of biomass and selective hydrolysis of cellulose microfibril (MFC)>

[0086] [Production Example 1] The biomass used for the preparation of lignin-cellulose microfibril (MFC) composites and the selective hydrolysis reaction of cellulose microfibril (MFC) was Korean pine, and the biomass was crushed so that the diameter of the biomass before acid treatment was less than 1 mm.

[0087] Then, the pine powder as biomass and water were added in a mass ratio of 1:10 to a Teflon-coated stainless steel reactor, and 3 wt% sulfuric acid based on the total mass of the added materials was further added. The reaction system was then stirred at 100°C for 10 minutes under closed conditions to produce a lignin-cellulose microfiber (MFC) composite.

[0088] The reaction temperature was then increased to 130°C, and the mixture was stirred and reacted for 60 minutes to obtain a solid reaction product. The resulting sample was washed twice with water, neutralized to pH 7.0 using 10N potassium hydroxide solution, and then washed twice with water again to obtain the final solid product. The washed solid product was then dried in a dryer at 70°C for 6 hours.

[0089] Figure 2 shows a photograph of the white fibrous portion and the brown particulate portion sampled together after drying and analyzed under an electron microscope. As shown in Figure 2, the white fibrous material was confirmed to be cellulose microfibers (MFC) with a thickness of about 100 nm to 1 μm. These lignin-cellulose microfiber (MFC) complexes were pulverized to further shorten the length of the cellulose microfibers (MFC) in the lignin-cellulose microfiber (MFC) complexes, producing a scratch-resistant additive.

[0090] FIG. 3 shows the results of an electron microscope analysis of the powder containing the lignin-cellulose microfiber (MFC) complex after the grinding process, which shows that the long fibrous structure of the cellulose microfiber (MFC) was destroyed by mechanical grinding and its length was shortened to the range of about 50 nm to 50 μm.

[0091] Meanwhile, Fig. 5 shows particle size analysis data of the solid powder after pulverization obtained by Production Example 1. Fig. 5 also shows that the particle size range of the obtained solid powder is 50 nm to 50 µm, which indirectly indicates that the length of the cellulose microfibril (MFC) is in the range of about 50 nm to 50 µm.

[0092] <Production of plastic test pieces containing the additive according to the present invention> <Example 1> Analytical test pieces were prepared using the resin composition shown in Table 1 below, to which the scratch-resistant additive prepared in Preparation Example 1 was applied at 5 wt %. The polymer resins used were LC170 manufactured by LG Chem for POE and H1500 manufactured by LG Chem for PP, Talc (KC300C, manufactured by KOCH) for filler, LYSI-306 (Lysi-306, Chengdu Silike Technology Co., Ltd.) for existing commercial scratch-resistant additive, and the additive according to Preparation Example 1 for the scratch-resistant additive according to the present invention.

[0093] Example 1 is intended to compare the performance of the scratch-resistant bio-additive prepared in Preparation Example 1 with the following Comparative Example 1 (negative control group) and Comparative Example 2 (positive control group) using PDMS (polydimethylsiloxane), an existing commercial scratch-resistant additive.

[0094] <Comparative Example 1 and Comparative Example 2> In Comparative Example 1, a test piece (negative control group) to which PDMS was not applied was prepared using the resin composition shown in Table 1 below. In Comparative Example 2, a test piece (positive control group) containing PDMS in the same content (5 wt%) as the scratch-resistant material prepared in Example 1 was prepared.

[0095] <Example 2> In Example 2, as shown in Table 1 below, the additive prepared in Preparation Example 1 was increased in the composition of Example 1 to prepare an analytical test piece containing 10 wt % of the additive prepared in Preparation Example 1.

[0096] The test specimens prepared in Example 2 are compared with Comparative Example 3 (negative control group) and Comparative Example 4 (positive control group) below in order to compare the weight of the test specimens and the performance when a portion of the talc used is replaced with the scratch-resistant additive of the present invention and the existing scratch-resistant additive PDMS is used.

[0097] <Comparative Example 3 and Comparative Example 4> In Comparative Example 3, as shown in Table 1 below, the content of Talc was increased (20 wt%) compared to Comparative Example 1 to match the total content (20 wt%) of Talc (10 wt%) and scratch resistance additive (10 wt%) according to Example 2 of the present invention, but a test piece (negative control group) was prepared without PDMS. In Comparative Example 4, a test piece (positive control group) was prepared in which 5 wt% PDMS was further added to the same as in Comparative Example 3.

[0098] [Experiment 1] Evaluation of scratch resistance properties of scratch resistance additives The following Table 1 summarizes the compositions, scratch resistance, and basic physical properties of the test pieces prepared in Example 1, Example 2, and Comparative Examples 1 to 4. The results shown in Table 1 are the average values ​​of the measured values ​​for five test pieces, and the test methods are as follows.

[0099] First, the basic physical properties were evaluated according to the ISO measurement methods in Table 1 below, and the scratch resistance was measured using an Elixens scratch tester based on the General Motors method GMW14688 for measuring scratch resistance of plastics. The Elixens scratch tester uses a color difference meter (spin sphere) to measure the L value before and after scratch evaluation, and calculates the ΔL value, with the lower ΔL indicating better scratch resistance.

[0100] [Table 1]

[0101] Referring to Table 1, when comparing the scratch resistance ΔL values ​​of Comparative Example 1, Comparative Example 2, and Example 1, it can be seen that the test piece to which the scratch resistance additive of Preparation Example 1 of the present invention was applied exhibited superior scratch resistance, which is shown in the photograph in Figure 4 (left and middle: Comparative Examples 1 and 2, right: Example 1).

[0102] In addition, when comparing the scratch resistance ΔL values ​​of Comparative Example 3, Comparative Example 4, and Example 2, it can be confirmed that the test piece to which the scratch resistance additive of Preparation Example 1 of the present invention was applied exhibits superior scratch resistance.

[0103] Furthermore, comparing the specific gravity measurements of Comparative Example 3, Comparative Example 4, and Example 2, it can be seen that the weight was reduced by about 4%. This can be seen as a result of the effect of substituting the scratch resistance additive of Experimental Example 1 (specific gravity 1.1) for the existing filler talc (specific gravity 2.7).

[0104] Talc, a conventional inorganic filler, has low binding strength with the polymer matrix and is easily separated due to deformation or damage of the surface, exposing white particles on the surface, which increases scratch visibility due to light reflection. As shown in Table 1, the scratch resistance additive of the present invention can be confirmed to be a multifunctional additive that improves scratch resistance while replacing existing high specific gravity inorganic fillers without significant changes in the basic physical properties of the comparative test specimens.

[0105] As described above, it has been confirmed that the scratch resistance of the surface of a plastic product made from a plastic composition containing the scratch resistance additive according to the present invention can be improved, and the weight of the product can also be reduced when replacing talc, an existing inorganic filler. [Industrial Applicability]

[0106] The present invention relates to a method for producing a scratch-resistant bio-additive for adding to plastics that replaces conventional high-density inorganic fillers and has improved scratch resistance, and to a scratch-resistant bio-additive for adding to plastics produced by the method, and has industrial applicability.

Claims

1. (a) adding an acid to lignocellulosic biomass to hydrolyze at least a portion of the hemicellulose in the lignocellulosic biomass and convert at least a portion of the cellulose into microfibrillated cellulose (MFC) to obtain a lignin-cellulose microfibrillated (MFC) composite; (b) selectively hydrolyzing at least a portion of the amorphous domains of the cellulose microfibril (MFC) in the lignin-cellulose microfibril (MFC) composite obtained from the (a) step to obtain a lignin-cellulose microfibril (MFC) composite having increased crystallinity of the cellulose microfibril (MFC); (c) adding a base to the lignin-cellulose microfiber (MFC) composite having improved crystallinity of the cellulose microfiber (MFC) obtained in the (b) step to neutralize the residual acidic components, and then removing the water-soluble substances to obtain solid particles; (d) grinding the solid particles obtained from step (c).

2. (a) adding an acid to lignocellulosic biomass to hydrolyze at least a portion of the hemicellulose in the lignocellulosic biomass and convert at least a portion of the cellulose into microfibrillated cellulose (MFC), and selectively hydrolyzing at least a portion of the amorphous domains of the cellulose microfibrillated cellulose (MFC) to produce a lignin-cellulose microfibril (MFC) composite having increased crystallinity of the cellulose microfibril (MFC); (b) adding a base to the lignin-cellulose microfibril (MFC) composite obtained in step (a) to neutralize residual acidic components, and then removing water-soluble substances to obtain solid particles; (c) grinding the solid particles obtained from step (b).

3. 3. The method for producing a scratch-resistant bio-additive for plastics according to claim 1 or 2, characterized in that in step (a), the acid is selected from the group consisting of an organic acid having 1 to 20 carbon atoms; an inorganic acid selected from sulfuric acid, hydrochloric acid, phosphoric acid, and nitric acid, or a mixture thereof; a mixture of the organic acid and an inorganic acid; or a mixture of the organic acid and an inorganic acid.

4. The method for producing the scratch-resistant bio-additive for plastics according to claim 1 or 2, characterized in that the step (a) is carried out by: i) adding an acid aqueous solution and heating and / or pressurizing the lignocellulosic biomass; ii) adding an acid aqueous solution and steam explosion; or iii) a combination of the heating and pressurizing treatment and steam explosion.

5. The method for producing the scratch-resistant bio-additive for plastics according to claim 1, wherein the step (b) is carried out under a higher temperature and / or pressure condition than the step (a).

6. The acid in the step (a) is any one selected from hydrochloric acid, sulfuric acid, and nitric acid, or a mixture thereof; The method for preparing a scratch-resistant bio-additive for plastics according to claims 1 and 2, characterized in that the acid is used at a concentration in the range of 0.5 to 70 wt %.

7. The base used in step (c) of claim 1 or step (b) of claim 2 is sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH) 2 ), ammonia (NH 3 ), lithium hydroxide (LiOH), calcium carbonate (CaCO 3 ), potassium carbonate (K 2 CO 3 ), sodium carbonate (Na 2 CO 3 ), potassium bicarbonate (KHCO 3 ), magnesium hydroxide (Mg(OH) 2 ), calcium oxide (CaO), magnesium oxide (MgO), and sodium bicarbonate (NaHCO 3 3. The method for producing the scratch-resistant bio-additive for plastics according to claim 1 or 2, characterized in that the bio-additive is at least one selected from the group consisting of fluororesin, fluorocarbons, fluoroisopropylacrylamide, fluorosuccinic acid, fluoroisopropylacrylamide ...

8. The solid particles obtained in step (c) of claim 1 or the solid particles obtained in step (b) of claim 2 have a hemicellulose content of 5 weight percent or less based on the total amount of lignin, cellulose, and hemicellulose-derived components.

9. The method for producing the scratch-resistant bio-additive for plastics according to claim 1 or 2, characterized in that the solid particles obtained in step (c) according to claim 1 contain 1 wt% to 99 wt% of lignin-derived components and 1 wt% to 99 wt% of cellulose-derived components based on the total amount of lignin, cellulose and hemicellulose-derived components.

10. The method for producing the scratch-resistant bio-additive for plastic additive according to claim 1 or 2, characterized in that the length of the cellulose microfibrils (MFC) in the pulverized solid particles from step (d) of claim 1 or the pulverized solid particles from step (c) of claim 2 is in the range of 50 nm to 100 μm.

11. 13. A scratch resistant bio-additive for plastics additive produced by the method of claim 1.

12. A scratch resistant bio-additive for plastics additive produced by the method of claim 2.

13. A lignin-cellulose microfibrillated (MFC) composite in which at least a portion of the cellulose is converted to cellulose microfibrillated (MFC) by acid treatment and neutralization of lignocellulosic biomass; Based on the total sum of lignin, cellulose and hemicellulose derived components, the composition contains 1 wt% to 99 wt% of a lignin derived component and 1 wt% to 99 wt% of a cellulose derived component; The hemicellulose content is 5% by weight (wt%) or less based on the total amount of lignin, cellulose, and hemicellulose-derived components; A scratch-resistant bio-additive for plastics additive, characterized in that the length of the cellulose microfibril (MFC) in the lignin-cellulose microfibril (MFC) composite is in the range of 50 nm to 100 μm.

14. A plastic composition comprising the scratch resistant bio-additive for plastics according to claim 13.

15. A scratch-resistant plastic composition comprising the scratch-resistant bio-additive for plastics according to claim 13 in an amount of 0.1 to 60% by weight based on the total weight of the composition.

16. A scratch resistant plastic article comprising the plastic composition of claim 15.

Citation Information

Patent Citations

  • Composition, laminate obtained by laminating the composition, and hard coating agent for forming the composition

    JP2015160870A

  • Cellulose-containing resin composition

    JP2019014865A

  • Powdery cellulose and method for producing the same, and use therefor

    JP2020164822A

  • Processes for producing nanocellulose-lignin composite materials, and compositions obtained therefrom

    WO2015200584A1

  • Resin composition and method for producing same

    WO2018012643A1